Correction of Postoperative Anemia in Patients undergoing Mitral Valve Replacement through Blood Saving Technology - Gumeniuk, B. M. (Ukrainian Journal of Cardiovascular Surgery, 2020)
The aim. To investigate anemia of chronic disease (ACD) in patients with mitral valvular disease, to provide preoperative correction in these patients and to determine the level of postoperative anemia after mitral valve replacement (MVR) through blood saving technology (BST) under artificial circulation (AC). Materials and methods. This is a study of 104 patients operated due to acquired mitral heart defects under AC. According to the baseline Hb, Ht, serum iron (SI) as well as the use of BST during MVR, all the patients were divided into 3 groups. Group A included 47 patients with normal Hb concentration, Ht and SI, who underwent the surgical intervention without BST with blood transfusion. Group B included 35 patients without ACD who were operated without blood transfusion with the use of BST. The group C included 22 patients with preoperative ACD with low Hb, Ht, and SI. A week before surgery the patients of group C underwent preoperative correction of SI and erythropoiesis stimulation using erythropoietin. The patients of group C were operated using BST. Preoperative correction of anemia and the use of blood and BST during surgery in groups A, B, C were compared. The effect of preoperative ACD correction and erythropoiesis stimulation on the level of postoperative anemia in patients operated due to mitral heart disease through BST in group C and with or without correction in group B was studied. Results. The presented research results show that in group A, in order to sufficiently stabilize the level of Hb and Ht during the operation, donated blood components (590.0 ± 83.0 ml of packed red blood cells and 563.0 ± 68.0 ml of fresh frozen plasma) were used. The use of BST in the group B reduced the level of Hb by 17.4%, Ht by 15.8%, thrombocyties by 20.5%, and the intervention could be performed without donated blood transfusion. Preoperative correction of SI and administration of erythropoietin in patients with ACD resulted in 8.6-fold increase in SI, 5.5-fold increase in ferritin and increase in Hb by 8.1% before the intervention. The use of BST and hematopoietic technology during MVR in patients of group C stabilized SI, Hb and platelets in the operative period, which facilitates operations under AC without transfusion of donated blood components. Conclusions. 1. In patients of group A, donor blood components (590.0 ± 83.0 ml of packed red blood cells and 563.0 ± 68.0 ml of fresh frozen plasma) were used to stabilize Hb and Ht during MVR without the use of BST. 2. ACD correction in patients of group C with mitral heart disease has led to a 8.6-fold increase in SI (p˂0.05), increase in transferrin saturation coefficient by 36.8% (p˂0.05), and 5.5-fold increase in ferritin activity (p˂0.05). 3. The use of BST in patients of group B undergoing MVR reduces the level of Hb by 17.4% (* p˂0.05) and platelets by 20.5% (* p˂0.05). 4. Preoperative correction of SI with iron (III) hydroxide and hemapoiesis stimulation by erythropoietin in patients of group C with MVR using BST reduces anemia by 10.7% and thrombocytopenia by 5%.